Single Input Multiple Output Voltage Mode Universal Filters with Electronic Controllability Using Commercially Available ICs - Pwint Wai, May Phu; Jaikla, Winai; Suwanjan, Peerawut; Sunthonkanokpong, Wisuit (My University, 2020)
This contribution presents the realization of commercially available ICs based single input voltage and three-output voltages universal second order filters with electronic controllability. Both proposed filters comprise two commercially available ICs LT1228, three passive resistors and two grounded passive capacitors. Two presented filters give low-pass (LP) voltage transfer function, band-pass (BP) voltage transfer function and high-pass (HP) voltage transfer function without modifying the scheme. The filtering parameters, center frequency (ω0) is tuned electronically as well as quality factor (Q) via controlling external DC bias currents. Moreover, the ω0 is linearly and electronically controlled without disturbing the Q by simultaneously changing bias currents. Using grounded capacitors are easy for the cancellation of parasitic element effects in LT1228s. The Pspice simulation and experimental results using integrated circuit, LT1228 are given to verify the filtering design.
Keywords: active building block; LT1228; SIMO; universal filter